#WarCrimes #PostConflictJustice #Balkans: Youth, Performance Activism and the Politics of Memory. (4th July 2016) - Kurze, Arnaud
ABSTRACT 1 : While literature in transitional justice has addressed conventional retributive and restorative justice mechanisms, scholarship focusing on the rise in youth activism to confront war crimes is underdeveloped. This article draws on over two-dozen in-depth interviews with youth activist leaders across the former Yugoslavia, focusing on their performance-based campaigns. I explain why the emergence of transitional justice youth activism in the Balkans falls short of the significant institutional reforms of earlier youth movement mobilizations in the region. I also throw light on why their performance activism is distinct from practices of older, established human rights organizations in the region. Notwithstanding, I argue that this performance-based advocacy work has fuelled the creation of a new spatiality of deliberation – so-called strategic confrontation spaces – to contest the culture of impunity and challenge the politics of memory in the former Yugoslavia.